WA INFLUENCE OF HYDROCARBON COMPOSITIONS OF THE HYDROCRACKING FEEDSTOCKS ON THE HYDROCRACKED PRODUCTS OF LUBRICANT BASE STOCK AND MIDDLE DISTILLATE - A.S. Nasution (Scientific Contributions Oil and Gas, 1987)
An experiment has been carried out to study to influence of hydrocarbon composition of the hydrocracking feedstocks on the hydrocracked products of lubricant base stock and middle distillate with bi-functional catalyst.  The operating conditions are;  temperature: from 400° to 420°C pressure: from 100 kg/cm2 and H2/HC ratio: 1000 Ilt/lt using a Catatest unit, operated with a continuous system.  Experimental data show that the high content of paraffin hydrocarbon in the hydrocracked feedstock tends to increase the viscosity index of lubricant base stock, smoke point of kerosene and diesel index of gas oil products.